An economic evaluation attached to a single-centre, parallel group, unmasked, randomized controlled trial of a 3-day intensive social cognitive treatment (can do treatment) in patients with relapsing remitting multiple sclerosis and low disability. (3rd October 2019) - van Mastrigt, Ghislaine A.; Evers, Silvia M.; Heerings, Marco; Visser, Leo H.; Ruimschotel, Rob P.; Hussaarts, Astrid; Duyverman, Lotte; Valkenburg-Vissers, Joyce; Cornelissen, Job; Bos, Michel; van Droffelaar, Maarten; Jongen, Peter J.
Abstract: Aims: This trial-based economic evaluation (EE) assesses from a societal perspective the cost-effectiveness of an intensive 3-day cognitive theory-based intervention (CDT), compared to care-as-usual, in patients with relapsing remitting multiple sclerosis (RRMS) and low disability (Expanded Disability Status Scale [EDDS] score < 4.0). Materials and methods: The trial of the EE was registered in the Dutch Trial Register: Trial NL5158 (NTR5298). The incremental cost-effectiveness ratio (ICER) was expressed in cost on the Control sub-scale of the Multiple Sclerosis Self-Efficacy Scale (MSSES) and the incremental cost-utility ratio (ICUR) in the cost per Quality Adjusted Life Years (QALY) using the EQ-5D-5L. Bootstrap, sensitivity, and sub-group analyses were performed to determine the robustness of the findings. Results: The two groups of 79 patients were similar in baseline characteristics. The base case ICER is situated in the northeast quadrant (€72 (40.74/€2, 948)) due to a higher MSSES Control score and higher societal costs in the CDT group. The ICUR is situated in the northwest (inferior) quadrant due to losses in QALY and higher societal costs for the CDT group (−0.02/€2, 948). Overall, bootstrap, sensitivity, and sub-group analyses confirm the base case findings. However, when the SF-6D is used as a study outcome, there is a high probability that the ICUR is situated in the northeast quadrant. Limitations: The relative short follow-up time (6 months) and the unexpected increase in MSSES Control in the control group. Conclusions: When using the EQ-5D-5L to calculate a QALY, CDT is not a cost-effective alternative in comparison to care as usual. However, when using self-efficacy or SF-6D as outcomes, there is a probability that CDT is cost-effective. Based on the current results, CDT for patients with RRMS clearly show its potential. However, an extended follow-up for the economic evaluation is warranted before a final decision on implementation can be made.